Implications of Basel III on the return of assets and return on equity of Universal Banks in the Philippines in relation to the upcoming ASEAN Integration - Germino, Princess Gracia V., Adan, Maria Francesca M., Banaag, Alexandra Isabel A., Catbagan, Sol Marie Ann S., Dela Cruz, Dominique Lyn A., Juruena, Jessica Lindsay P., Navasca, Mary Antonette R., Reformina, Ivan kim S., Sangle, Marjorie M., Villa, John Maverick E. 4 0 16; 5 (2016)
u
Research Paper: (BSBA major in Finance and Treasury Management) - Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2